(3TQM GdebfYs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s ((3YHO Gddg Hf eMeO GdeZQHi GdeGdci s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg aGdZQV GNJUGQ GdebfY djSgd Ydi ef bUQJ geJg JfGhdg s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1809s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs